Quantification of Proton Dose Calculation Accuracy in the Lung - Grassberger, Clemens (2014)
PURPOSE: Quantify the accuracy of a clinical proton treatment planning system (TPS) as well as Monte Carlo (MC) based dose calculation through measurements. Assess the clinical impact in a cohort of patients with tumors located in the lung. METHODS: A lung phantom and ion chamber array were used to measure the dose to a plane through a tumor embedded in lung and to determine the distal fall-off of the proton beam. Results were compared with TPS and MC calculations. Dose distributions in 19 patients (54 fields total) were simulated using MC and compared to the TPS algorithm. RESULTS: MC increases dose calculation accuracy in lung tissue compared to the TPS and reproduces dose measurements in the target to within ±2%. The average difference between measured and predicted dose in a plane through the center of the target is 5.6% for the TPS and 1.6% for MC. MC recalculations in patients show a mean dose to the clinical target volume on average 3.4% lower than the TPS, exceeding 5% for small fields. For large tumors MC also predicts consistently higher V5 and V10 to the normal lung, due to a wider lateral penumbra, which was also observed experimentally. Critical structures located distal to the target can show large deviations, though this effect is very patient-specific. Range measurements show that MC can reduce range uncertainty by a factor ~2: the average(maximum) difference to the measured range is 3.9mm(7.5mm) for MC and 7mm(17mm) for the TPS in lung tissue. CONCLUSION: Integration of Monte Carlo dose calculation techniques into the clinic would improve treatment quality in proton therapy for lung cancer by avoiding systematic overestimation of target dose and underestimation of dose to normal lung. Additionally, the ability to confidently reduce range margins would benefit all patients through potentially lower toxicity.